2015
DOI: 10.7554/elife.03189
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional response to tumorigenic polarity loss in Drosophila

Abstract: Loss of polarity correlates with progression of epithelial cancers, but how plasma membrane misorganization drives oncogenic transcriptional events remains unclear. The polarity regulators of the Drosophila Scribble (Scrib) module are potent tumor suppressors and provide a model for mechanistic investigation. RNA profiling of Scrib mutant tumors reveals multiple signatures of neoplasia, including altered metabolism and dedifferentiation. Prominent among these is upregulation of cytokine-like Unpaired (Upd) lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
186
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(208 citation statements)
references
References 76 publications
15
186
0
Order By: Relevance
“…Previous reports and our studies demonstrate that the JAK/STAT ligands upd1, upd2 and upd3 are transcriptionally upregulated in response to stress from physical injury (Katsuyama et al, 2015;Pastor-Pareja et al, 2008) or tumorous growth (Wu et al, 2010;Bunker et al, 2015), indicating that pathway upregulation may be driven by JNK-dependent Upd gene transcription. We found that transcription of Upd genes is highly elevated in Eiger-stimulated discs, whereas transcription of dome, hop and Stat92E is not (Fig.…”
Section: Unpaired Ligands Are Upregulated Upon Eiger-induced Tissue Dsupporting
confidence: 59%
See 3 more Smart Citations
“…Previous reports and our studies demonstrate that the JAK/STAT ligands upd1, upd2 and upd3 are transcriptionally upregulated in response to stress from physical injury (Katsuyama et al, 2015;Pastor-Pareja et al, 2008) or tumorous growth (Wu et al, 2010;Bunker et al, 2015), indicating that pathway upregulation may be driven by JNK-dependent Upd gene transcription. We found that transcription of Upd genes is highly elevated in Eiger-stimulated discs, whereas transcription of dome, hop and Stat92E is not (Fig.…”
Section: Unpaired Ligands Are Upregulated Upon Eiger-induced Tissue Dsupporting
confidence: 59%
“…JAK/STAT activity is not required for compensatory proliferation JAK/STAT has been reported to play a role in promoting cell proliferation in wild-type (Bach et al, 2003;Tsai and Sun, 2004;Mukherjee et al, 2005), tumorous (Classen et al, 2009;Wu et al, 2010;Davie et al, 2015;Bunker et al, 2015;Amoyel et al, 2014) and surgically injured discs (Katsuyama et al, 2015). To test whether JAK/STAT is generally required to drive compensatory proliferation, we quantified mitotic events after Eiger stimulation in discs with impaired JAK/STAT signalling.…”
Section: Unpaired Ligands Are Upregulated Upon Eiger-induced Tissue Dmentioning
confidence: 99%
See 2 more Smart Citations
“…To fine-tune the read-out of our study, we included two other genes encoding cytokines, upd1 and upd3, which are known to be induced by both JNK and/or Yki signaling in ECs following ingestion of Pe or large amounts of Ecc and to be responsible for ISC proliferation upon damage (Buchon et al, 2009a,b;Bunker et al, 2015;Jiang et al, 2009;Karpowicz et al, 2010;Osman et al, 2012;Patel et al, 2015;Ren et al, 2010;Shaw et al, 2010;Staley and Irvine, 2010). We found that small amounts of Btk activated upd1, but not upd3, whereas small amounts of Ecc activated upd1 (although not significant in our statistical test) and upd3 (Fig.…”
Section: Resultsmentioning
confidence: 99%